PENGARUH VARIASI KONSENTRASI EKSTRAK ETANOLIK DAUN TEH HIJAU (Camelia sinensis L.) DALAM SEDIAAN KRIM TERHADAP SIFAT FISIK DAN AKTIVITAS ANTIBAKTERI - nanik widyaningrum; mimik murrukmihadi; syarifatun karuniaekawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2009)
ABSTRACTGreen tea is one of a herbal nature which has been proved its special virtue anti acne. Green tea leafcontains of 30-40% polifenol which is known as katekin has a characteristic as antimicroba.To make it easierto use, the extrac etanolic of green tea leaf is made in cream formulation. The purpose of this experiment is toknow variation concentration effect of green tea etanolic extract in cream formulation to the physic andantibacteria activity especially for the acne bacteria, also in spesific concentration will be find the best ofextrac etanolic green tea leaf toward physic characteristic and anti bacterial activity.In this experiment, the thick extrac of green tea leaf is obtained by maseration way of the using 50%etanol liquid. The cream is made in five formulas that is using the extrac etanolic of green tea leaf for 1%, 3%,5%, 7% and 9% concentration with the modification formula of anti acne cream. Cream is tested the physicalcharacteristic including the homogenity , isolation percent, spreading, and adhesing and also for antibacterialactivity. The data is analysed by non parametric statistical using Kruskal Wallis test continued by doing MannWhitney test with 95% of trust capacity.The result in this experiment showes that the cream of extrac etanolic form of green tea leaf in anycream concentration have good homogenity and did not isolation. As biger concentration of cream extracetanolik of green tea leaf as a smaller spreading test and adhesing test but as a biger antibacterial activitytoward Staphylococcus aureus bacterial. Cream extrac etanolik of green tea leaf as a control positive in physiccharacteristic and antibacterial activity is 7% concentration.Key words : Green tea of extract etanolic, Cream, Physic characteristic test, Bacterial activity test.